A Study on the Dyslipidemia in Type II Diabetic Patients with and without Microalbuminuria - Urooj Mehtab Raina, Arbab Nisar, Muhammad Kashif Bashir, Habib Ur Rehman, Shoaib Liaquat, Omar Shahid (Pakistan Journal of Medical & Health Sciences, 2022)
Objective: To record the rate of microalbuminuria in cases with type II diabetic mellitus and to record the frequency of dyslipidemia in cases with microalbumina and without it. Methodology: This study was conducted at Sheikh Zayed Hospital Rahim Yar Khan from July 2021 to December 2021 a total of 80 cases with type-II diabetes mellitus, between 35-70 years of age of either gender was enrolled whereas those having microalbuminuria, increased levels of serum creatinine with the history of CVD, UTI and pregnant females were excluded. Blood samples in a disposable syringe were obtained to determine microalbuminuria and with 12 hours fasting time for evaluation of hyper triglycerides, HDL-C, LDL-C in positive and negative cases of microalbuminuria. Results: In this study, 35%(n=30) were between 35-50 years of age whereas 45%(n=50) were between 51-70 years of age, Mean+SD was calculated as 55.43+7.66 years, male cases were 48%(n=48) whereas 32%(n=32) were females. Presence of microalbuminuria was recorded in 29%(n=25). Comparison for presence of dyslipidemia in diabetic cases with and without microalbuminuria shows that 91.8%(n=27) in microalbuminuria and 57.13%(n=32) in cases without it had hypertriglyceridemia, p value was 0.0009, increased LDL-C was recorded in 84.19%(n=25) in microalbuminuria group whereas 59.95%(n=44) had in cases without microalbuminuria, p value was 0.017, decreased DHL-C level were recorded in 80.74%(n=24) in microalbuminuria group and 72.63%(n=53) without it, p value was 0.38. Conclusion: The rate of microalbuminuria in cases with type II diabetes is not uncommon while these cases had higher risk of dyslipidemia when compared to those without it.